Pengaruh Akuntabilitas, Independensi, dan Pengalaman Kerja Terhadap Kualitas Audit - Muhammad Dandy Akbar; Dian itria Handayani (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to examine the influence of accountability, independency, and work experience on audit quality at Public Accounting Firms in Padang City. Primary data was obtained from questionnaires filled out by respondents. The sample used in this research was the auditors of the Public Accounting Firm in Padang City, totaling 60 people. The statistical data analysis technique used in this research in multiple regression analysis. The research results show that accountability has a significant positive effect on audit quality at the Public Accounting Firm in Padang City. Meanwhile, independency and work experience have no effect on audit quality at the Public Accounting Firm in Padang City. The implication of this research is in the form of relevant information that companies and auditors should maintain credibility in preparing financial reports so as not to harm the entity, auditor and third parties. Therefore, correct and precise information is needed from the results of an audit of a client's financial statements in a company, this will determine the decisions that will be taken, such decisions as granting credit, investment, acquisitions, and so on. This audited financial report will be provided to the party who requires the results, where it will be used for making decisions in the company.